An evaluation of academic achievements through the use of argument and concept maps embedded in argumentation based inquiry - KABATAŞ MEMİŞ, Esra; KARAKUŞ, Esma (Springer Science and Business Media LLC, 2021)
This mixed-method study aimed to compare the academic achievements of students to their use of argument maps and concept maps in learning environments designed for argument-based instruction (ABI). The study was conducted during the spring term of the academic year 2018–2019 with the students of three sections of grade six instructed by the same teacher at a secondary school in the province of Kastamonu. Before the study began, one of the participating sections was randomly designated as the control group, while the other two were assigned as the experimental group. The control group students undertook research interrogation-based activities during lessons and individually reported activities appropriate for the ABI student template for each activity. The experimental group students handled ABI applications. In addition, one section of the experimental group prepared concept maps, while the other section made argument maps. The 5-week study was accomplished during the instruction of the “sound and its properties” unit of the curriculum. The data were acquired via a pre- and post-administration of the unit-based success test to measure academic success. Further, semi-structured interviews were conducted to ascertain the opinions of students vis-a-vis the pedagogy. The obtained quantitative data were analyzed using the ANCOVA analysis via the SPSS software. The qualitative data collected through semi-structured interviews were examined by the creation of themes, codes, and frequencies. The experimental group using argument maps or concept maps in addition to ABI applications revealed significant outcomes in terms of academic achievements. Further, students expressed the belief that argument and concept maps helped them learn and remember the topic.
Keywords: 4. Education; 16. Peace & justice; 3. Good health